Evaluación del aislamiento acústico de materiales constructivos de un edificio residencial de la ciudad de Quito - Zaldumbide Burbano, Melany Alejandra (2018)
The following document objective is to analyze the results obtained in an on site investigation in a new residential building in the city of Quito, based on field acoustic measurements to be able to make a comparison with international acoustic insulation standards in residential buildings. In order to obtain results, the acoustic insulation regulations UNE EN ISO 16283 1, 16283 2 and 16283 3, 717 1 and 717 2, corresponding to the isolation of air noise, impact noise and frontage noise, will be used as reference, respectively. The instruments used to carry out these measurements were CESVA sound level meter, CESVA impact machine, omnidirectional source, power amplifier and noise generator. After obtaining the results based on the Spanish acoustics regulations and analyzing them, it was concluded that 5 out of 12 tests satisfy the proposed regulations.